Sosial Hukum dan Keadilan Untuk Semua: Menggugah Kesadaran Hukum pada Masyarakat Cahaya Negeri - Romanza, Melli; Eceh Trisna Ayuh; Titi Darmi (Program Studi Administrasi Fakultas Ilmu Sosial dan Ilmu Politik Universitas Muhammadiyah Bengkulu, 2024)
Legal awareness within society is a key factor in establishing a just and orderly social structure. Unfortunately, in Indonesia, legal awareness remains relatively low, as reflected in the frequent legal violations occurring in both private and public spheres. The program